Relationship Among Siblings in Portuguese Versions of the Pan-Hispanic Ballad Delgadinha - Paiva Morão, Ana Maria (Tautosakos darbai, 2020)
Delgadinha (IGR 0075) is one of the most widespread ballads (romances) in the pan-Hispanic world (Portuguese and Spanish-speaking communities and Sephardies) and perhaps one of the most studied, as many scholars have produced articles about it from different perspectives. The present study is a literary analysis of the ballad, considering some anthropological and sociological aspects. It focuses on Portuguese versions, also bearing in mind the other pan-Hispanic branches and features, mainly the part of Delgadinha’s narrative concerning the reactions of the girl’s siblings towards her situation. The theme of Delgadinha is an attempted father / daughter incest. When she refuses, her father locks her in a tower providing her with salty food and limited or brackish water. The girl desperately begs every family member for water but none of them helps in any way. When she finally tells her father that she will give in, he sends her a jar of clear water, but the girl is already dead when it arrives. This paper analyses the different excuses and arguments invoked by siblings in refusing help, grouping them by type. It studies the variation of this conduct in order to understand the siblings’ relationship within the family structure and the world of the ballad.